2014
DOI: 10.1001/jamafacial.2014.283
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electromyographic Mapping of the Orbicularis Oculi Muscle for Real-Time Blink Detection

Abstract: IMPORTANCE Facial paralysis is a life-altering condition that significantly impairs function, appearance, and communication. Facial rehabilitation via closed-loop pacing represents a potential but as yet theoretical approach to reanimation. A first critical step toward closed-loop facial pacing in cases of unilateral paralysis is the detection of healthy movements to use as a trigger to prosthetically elicit automatic artificial movements on the contralateral side of the face.OBJECTIVES To test and to maximize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Orbicularis‐oris activity, when pressing lips together, also evokes activation in other peri‐oral muscles (ie, depressor anguli oris, depressor labii, and mentalis) . Orbicularis‐oculi activity, the performance of blink detection, is better at the superomedial quadrant than at the inferolateral quadrant . It seems that the superomedial quadrant activity is associated with movements of both frontalis and temporalis muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbicularis‐oris activity, when pressing lips together, also evokes activation in other peri‐oral muscles (ie, depressor anguli oris, depressor labii, and mentalis) . Orbicularis‐oculi activity, the performance of blink detection, is better at the superomedial quadrant than at the inferolateral quadrant . It seems that the superomedial quadrant activity is associated with movements of both frontalis and temporalis muscles.…”
Section: Discussionmentioning
confidence: 99%
“…41 Orbicularis-oculi activity, the performance of blink detection, is better at the superomedial quadrant than at the inferolateral quadrant. 42 It seems that the superomedial quadrant activity is associated with movements of both frontalis and temporalis muscles. Thus, it is suggested that orbicularis-oculi contractions can induce headaches, whereas orbicularis-oris contractions may not tend to cause the symptoms at the superomedial quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the existing studies, A. Frigerio et al 4) proposed a measurement method especially for the orbicularis oculi muscle. N. P. Schumann et al 5) analyzed the movement of the muscles during has recommended sensor locations and placements in various muscles.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…sEMG is non-invasive, painless, and the number of surface electrodes used and therefore the number of facial muscles analyzed simultaneously, is unlimited. sEMG allows a detailed analysis of the coordinated muscle activation needed for specific tasks and emotional expressions [45,46]. If several surface electrodes are placed on the same facial muscle, the intramuscular pattern of muscle recruitment can be analyzed.…”
Section: Surface Electromyography (Semg)mentioning
confidence: 99%